From conscious experience to a conscious self. (2nd April 2016) - Sridharan, Vishnu
Abstract: In his book The Opacity of Mind, Peter Carruthers (2011 ) presents the Interpretive Sensory Awareness theory ("ISA"), which holds that while we have direct access to our own sensory states, our access to "self-knowledge" is almost always interpretive. In presenting his view, Carruthers also claims that his account is the first of its kind; after a cursory examination of major theories of mind, he concludes that "transparent access" accounts of self-knowledge—the alternative to ISA—have been endorsed throughout history. This paper challenges this latter claim. Contrary to Carruthers' view, the paper argues that Buddhist theories of mind are not "transparent access" accounts. Instead, they not only have an analysis of sensory processing and conscious experience similar to that of ISA, but also share what Carruthers sees as ISA's central tenet: individuals lack transparent, conscious access to most of their propositional attitudes. Given this fundamental alignment, the Buddhist perspective can offer us fresh responses to ISA's critics, as well as approaches to ethics and free will that are aligned with ISA's conclusions.